Fostering gerontology students’ competence in Interprofessional collaborative practice - Janita Pak Chun Chau; Suzanne Hoi Shan Lo; Vivian Wing Yan Lee; Wai Ming Yiu; Helen Chung Yan Chiang; David R. Thompson; Alexander Yuk Lun Lau (BMC Medical Education, 2020)
Abstract Background Interprofessional collaborative practice (IPCP) is increasingly recognised as being crucial for the provision of holistic care and optimising health outcomes among older adults, many with multiple complex health problems. However, little is known about the challenges of facilitating this in practice. Therefore, this study explores these issues from the perspective of different healthcare professionals and how this might inform interprofessional education curricula. Methods Sixteen different healthcare professionals working in a variety of aged care (acute, rehabilitative and community) settings were invited to participate in individual semi-structured in-depth interviews designed to: (i) explore the meaning of IPCP; (ii) explore the facilitators of and barriers to IPCP; and (iii) examine the opportunities and challenges in interprofessional gerontological education. All interviews were tape-recorded and transcribed verbatim with thematic analysis conducted by two independent researchers. Results Three major themes emerged from the interviews: the need for IPCP; role preparedness, scope and liability; and strategies for interprofessional education. Respondents shared a common belief that IPCP improves the quality of life of older adults in both hospital and community settings by improving person-centred coordinated care and decision making in care planning. However, respondents perceived major barriers to IPCP to be lack of knowledge about healthcare professionals’ scope of practice, lack of training in interprofessional collaboration, professional culture and stereotypes, and liability issues. Suggested approaches to overcome these barriers included innovative teaching and learning approaches, engaging students early on in the curriculum of health professional degree programmes, and enhancing collaborative effective communication in health and social care settings. Conclusions It is anticipated that these findings will be used to inform the development of a new interprofessional gerontological education curriculum that aims to enhance students’ competence in IPCP.